Mycobacterium avium subspecies paratuberculosis infection and autoimmune condition: investigation of family members - Margherita Sisto; Massimo D’Amore; C.Thomas Dow; Sabrina Lisi (Microbiologia Medica, 2009)
Mycobacterium avium subspecies paratuberculosis (MAP) causes Johne’s disease, a chronic granulomatous intestinal condition which affects ruminants, including cattle, sheep, goats, and farmed deer. In more recent studies water and milk supplies have both been suggested as vehicles of MAP transmission between cattle and humans. Recently our group observed immune responses to MAP in an Italian patient with Hashimoto’s thyroiditis and Melkersson-Rosenthal syndrome.The focus of our work was evaluate the hypothesis of a possible MAP infection in other members of the same family.